Effect of Pilates training on hepatic fat content and liver enzymes in middle-aged men with non-alcoholic fatty liver disease - ZIBA KEYMASI; ABBAS SADEGHI; HASSAN POURRAZI (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: ‪The objective of this study is to investigate the effects of eight weeks' Pilates training on the hepatic fat content and liver enzymes in middle-aged men with non-alcoholic fatty liver disease (NAFLD). Material and methods: T‪wenty middle-aged men with NAFLD were randomly divided into Pilates training (n = 10) and control (n = 10) groups. The Pilates group participated in the Pilates training program for eight weeks (three sessions per week, 60 minutes per session). The body composition, anthropometric indices, liver fat content, and serum levels of ALT, AST, and ALP were measured before and after the training period. Results: A‪fter eight weeks of Pilates training, the liver fat content in the Pilates group was significantly lower than that of the control group (P = 0.001). Also, the serum levels of ALT, AST, and ALP significantly decreased in the Pilates group, compared to the controls (P < 0.05). In addition, eight weeks of Pilates training significantly reduced the patients' body weight, body mass index (BMI), fat percentage, and the waist-to-hip ratio (P < 0.05). Conclusions: ‪The results of the present study indicated that Pilates training could be effective in improving the liver fat content and reducing the serum levels of ALT, AST, and ALP in middle-aged men with NAFLD.